2009
DOI: 10.1016/j.jcomdis.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-speaker variability in palatometric measures of consonant articulation

Abstract: The reader will be able to: (1) Describe how articulatory performance and variability can be assessed with the palatometer; (2) Describe which sounds are typically most or least variable in their production; and (3) Understand the significance of individual speaker differences in normal consonant articulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Honda, Maeda, Hashi, Dembowski, and Westbury (1996) demonstrated that the individual oral morphology has a clear impact on the articulatory strategies for vowels. Research has also shown that speakers may use markedly different articulatory strategies for consonant sounds, particularly for /l/, /r/, and /s/ (Dromey and Sanders, 2009). It is plausible that differences in orofacial morphology and habitual articulation patterns may have contributed to the differences that were observed between the speakers.…”
Section: Discussionmentioning
confidence: 99%
“…Honda, Maeda, Hashi, Dembowski, and Westbury (1996) demonstrated that the individual oral morphology has a clear impact on the articulatory strategies for vowels. Research has also shown that speakers may use markedly different articulatory strategies for consonant sounds, particularly for /l/, /r/, and /s/ (Dromey and Sanders, 2009). It is plausible that differences in orofacial morphology and habitual articulation patterns may have contributed to the differences that were observed between the speakers.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the breadth of these studies, it wasn't until recently that researchers examined variability in lingua-palatal contact patterns across and within normal speakers. EPG data generated by 20 individuals uttering vowel-consonant -vowel articulatory stimuli were analyzed by Sanders [12] in an unpublished thesis; and later by Dromey and Sanders [13]. The participants in their studies had no reported history of speech or language disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although past research has focused on EPG studies and acquired glossectomy, no studies to date have investigated EPG and intraoral articulatory constrictions of a PWCA. This article, the fifth in the series on the PWCA, investigates the unique speech production of this 44-year old female born without a tongue, and compares these patterns with those published by Dromey and Sanders [13]. For a full review of past papers published on this PWCA, please see McMicken et al [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…7 Alternatively, palatometry could reveal important aspects of linguapalatal contact in singers. 8 Future work could also evaluate the impact of biofeedback on the process of vowel equalization. For example, a real-time formant tracking system that plots F 1 against F 2 could provide individual singers the visual feedback necessary to monitor the progress of their equalization while practicing.…”
Section: Resultsmentioning
confidence: 99%